Joel Kaye. A History of Balance 1250-1375. The Emergence of a New Model of Equilibrium and its Impact on Thought (Cultura Económica, 2019)
Joel Kaye. A History of Balance 1250-1375. The Emergence of a New Model of Equilibrium and its Impact on Thought. Cambridge University Press – Cambridge, 2014. ISBN: 1107028450